Fumigant Activity of Bacterial Volatile Organic Compounds against the Nematodes Caenorhabditis elegans and Meloidogyne incognita - Diyapoglu, Ali; Chang, Tao-Ho; Chang, Pi-Fang Linda; Yen, Jyh-Herng; Chiang, Hsin-I; Meng, Menghsiao (Molecules (Basel, Switzerland), 2022)
Plant-parasitic nematodes infect a diversity of crops, resulting in severe economic losses in agriculture. Microbial volatile organic compounds (VOCs) are potential agents to control plant-parasitic nematodes and other pests. In this study, VOCs emitted by a dozen bacterial strains were analyzed using solid-phase microextraction followed by gas chromatography–mass spectrometry. Fumigant toxicity of selected VOCs, including dimethyl disulfide (DMDS), 2-butanone, 2-pentanone, 2-nonanone, 2-undecanone, anisole, 2,5-dimethylfuran, glyoxylic acid, and S-methyl thioacetate (MTA) was then tested against Caenorhabditis elegans. DMDS and MTA exhibited much stronger fumigant toxicity than the others. Probit analysis suggested that the values of LC50 were 8.57 and 1.43 μg/cm3 air for DMDS and MTA, respectively. MTA also showed stronger fumigant toxicity than DMDS against the root-knot nematode Meloidogyne incognita, suggesting the application potential of MTA.